Copper nanoparticles coating on FTO with improved adhesion using direct and pulse electrodeposition techniques from a simple copper sulphate solution - Nur Azlina Adris; Lorna Jeffery Minggu; Khuzaimah Arifin; Rozan Mohamad Yunus; Mohamad Azuwa Mohamed; Masliana Muslimin; Mohammad Kassim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Copper (Cu) metal nanoparticles were deposited onto FTO glass using the electrodeposition method. The precursor used was CuSO4 ⋅5H2 O with Na2 SO4 as the inorganic additive. The formation of Cu was characterized using field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). This study investigated the impacts of the electrodeposition method (direct electrodeposition vs. pulse electrodeposition), voltages (-0.4 V and -0.8 V), electrodeposition time (60s to 900s) and pulse cycles (50 cycles to 300 cycles), and FTO etching (fixed to 20s etching) towards the morphology and adhesion of Cu deposited. The grain size and thickness of Cu deposited vary with deposition time and pulse cycles. The voltage of -0.4 V successfully deposits shiny, metallic brown Cu onto FTO glass. Meanwhile, the voltage of -0.8 V gives powdery brown Cu on the surface. In addition, compared to direct electrodeposition (DD), pulse electrodeposition (PD) provides a more compact and homogeneous coverage of Cu onto FTO glass. The tape-test results also indicate that FTO etching by electrolysis reduction can improve the adhesion strength between deposited thin Cu film and the FTO glass. This work demonstrates a facile electrodeposition technique with substrate etching as an effective deposition of Cu metal with the potential for application in a wide range of fields.